FDR and the Soviet Union : The President's Battles over Foreign Policy - Glantz, Mary E. (Book collections on Project MUSE., 2005)
"A case study in foreign relations, high-level policymaking, and civil-military relations, FDR and the Soviet Union enlarges our understanding of the ideologies and events that set the stage for the Cold War. It adds a new dimension to our understanding of Soviet-American relations as it sheds new light on the surprising power of those in low places."--Jacket.